Distinct temporal trajectories and risk factors for Post-acute sequelae of SARS-CoV-2 infection - Chen, Chen; Parthasarathy, Sairam; Leung, Jacqueline M.; Wu, Michelle J.; Drake, Katherine A.; Ridaura, Vanessa K.; Zisser, Howard C.; Conrad, William A.; Tapson, Victor F.; Moy, James N.; deFilippi, Christopher R.; Rosas, Ivan O.; et al. (Frontiers in Medicine, 2023)
Background The understanding of Post-acute sequelae of SARS-CoV-2 infection (PASC) can be improved by longitudinal assessment of symptoms encompassing the acute illness period. To gain insight into the various disease trajectories of PASC, we assessed symptom evolution and clinical factors associated with the development of PASC over 3 months, starting with the acute illness period. Methods We conducted a prospective cohort study to identify parameters associated with PASC. We performed cluster and case control analyses of clinical data, including symptomatology collected over 3 months following infection. Results We identified three phenotypic clusters associated with PASC that could be characterized as remittent, persistent, or incident based on the 3-month change in symptom number compared to study entry: remittent (median; min, max: −4; −17, 3), persistent (−2; −14, 7), or incident (4.5; −5, 17) (p = 0.041 remittent vs. persistent, p < 0.001 remittent vs. incident, p < 0.001 persistent vs. incident). Despite younger age and lower hospitalization rates, the incident phenotype had a greater number of symptoms (15; 8, 24) and a higher proportion of participants with PASC (63.2%) than the persistent (6; 2, 9 and 52.2%) or remittent clusters (1; 0, 6 and 18.7%). Systemic corticosteroid administration during acute infection was also associated with PASC at 3 months [OR (95% CI): 2.23 (1.14, 4.36)]. Conclusion An incident disease phenotype characterized by symptoms that were absent during acute illness and the observed association with high dose steroids during acute illness have potential critical implications for preventing PASC.